In vitro degradation of fresh forage by ruminal anaerobic fungi (2004)
Important role as fibre degraders in the rumen ecosystem, Fungal rhizoids, Enzymes. Unusual group of fungi, strict anaerobes. Phylum: Neocallimastigomycota, Six genera currently recognised.